Otonomi Daerah, Primordialisme dan Sumber Daya Manusia - Andress Denny Bakarbessy (SASI, 2012)
The implementation of decentralization which is yielding autonomy aim to take care ofthe identity local, creating democratization, the make-up and build up the quality of publicservices so that is appearing the activity of the governance from top level to bottom level in order to serves various society's necessary. But the reality show that decentralization had been made up primordial sense or local sentiment, which is not controlled therefore madeup authorizeres of leadership who only carrying out their group necessary, so that diregarded public service progressively made down the social's prosperity